Effects of the German Renewable Energy Act on structural change in agriculture – The case of biogas. (August 2016) - Appel, Franziska; Ostermeyer-Wiethaup, Arlette; Balmann, Alfons
Abstract: The strong political support for biogas production in Germany over the past decade has greatly affected agricultural production, farms and land markets. This paper analyzes the effects of Germany's biogas policies on agricultural development by using the agent-based simulation model AgriPoliS. Particular focus is placed on the effects of the previous German Renewable Energy Act (REA, German "EEG") of 2012, as well as the latest amendments, which were added in 2014. Our results show that under the previous REA and its predecessors, biogas production provided an attractive investment opportunity, especially for large farms, which led to a boost in biogas production. However, this policy also caused distortions within the agricultural sector, including increasing land rental prices. These effects particularly threatened farms that were not able to invest in biogas, as well as smaller biogas farms. On average, biogas farms could not increase their profitability. The main reason for this effect can be seen in the fact that a significant share of the value added is transferred via increased rental prices to land owners. The amendment of the REA in 2014, which reduced support levels substantially, partly attenuates some of these effects, though the previous policy will cast a long shadow. Highlights: Analyzing effects of biogas policies on agriculture by using an agent-based model. Biogas is an attractive investment opportunity, especially for large farms. Biogas policy affects structural change, cultivation patterns and land markets. On average, biogas farms could not increase their profitability. The amendment of the REA in 2014 only partly attenuates some of these effects.